FESTA: Flexible Exon-based Splicing and Transcription Annotation - Rago, Alfredo; Colbourne, John Kenneth (bioRxiv, 2018)
We introduce FESTA, an R based algorithm that allows detection of alternative splicing based on experiment-specific exon expression data. FESTA disentangles alternative splicing signal from whole-gene transcription, facilitating the discovery and characterization of novel regulatory events even in the absence of transcript annotations or paired-end data. We also include customization options to increase its applicability on different platforms and experimental designs as well as a tool for the conversion from transcript expression to inclusion ratios.